2021
DOI: 10.3390/en14134032
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of a Novel Dual Layered Phase Change Material Brick Wall for Human Comfort in Hot and Cold Climatic Conditions

Abstract: Phase change materials (PCMs) have a large number of applications for thermal energy storage (TES) and temperature reduction in buildings due to their thermal characteristics and latent heat storage capabilities. The thermal mass of typical brick walls can be substantially increased using a suitable PCM primarily based on phase change temperature and heat of fusion for different weather conditions in summer and winter. This study proposed a novel dual-layer PCM configuration for brick walls to maintain human c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Both of these parameters are important in thermal comfortability analysis. Besides, the peak temperature reduction in the case of using PCM and the one that combining PCM with rockwool are the same 2 °C compared to the control set (brick only), therefore Experimental results [33] 16th…”
Section: Compare Pcm With Rockwoolmentioning
confidence: 87%
See 3 more Smart Citations
“…Both of these parameters are important in thermal comfortability analysis. Besides, the peak temperature reduction in the case of using PCM and the one that combining PCM with rockwool are the same 2 °C compared to the control set (brick only), therefore Experimental results [33] 16th…”
Section: Compare Pcm With Rockwoolmentioning
confidence: 87%
“…Besides, to setup the boundary conditions, a transient table with hourly temperature profile on 23 rd and 24 th February 2021 is inserted into the software as input of the 1D heat transfer from outdoor surface to indoor surface [25]. The heat transfer across the surface that in contact with outdoor air is taken as natural convection with heat transfer coefficient of 14 W/m 2 [33] whilst other surface are assumed adiabatic with zero heat flux. Apart from that, SIMPLE algorithm was applied for the pressure-velocity coupling, and the equations were all discrete from second order upwind scheme.…”
Section: Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, very limited studies have reported using ANSYS (Fluent) to simulate the melting and freezing of CaCl26H2O or other PCM. Previous studies by Fiala et al [5], Rehman et al [6], and Wang et al [7] focus on the melting behaviour of CaCl26H2O. In addition, through an intensive study, Pan et al [8] have shown the agreement between the result of Numerical/simulation and experimental for comparing the melting patterns of CaCl26H2O confined in a vertical tube submerged in a water bath.…”
Section: Introductionmentioning
confidence: 95%